Pulsed Gate Switching of MoS2 Field‐Effect Transistor Based on Flexible Polyimide Substrate for Ultrasonic Detectors. (17th November 2020) - Naqi, Muhammad; Kim, Bosung; Kim, Sang‐Woo; Kim, Sunkook
Abstract: Molybdenum disulfide (MoS2 ) semiconductors have closely been studied for potential applications in detectors, optoelectronics, and flexible electronics due to its high electrical and robust mechanical performance. Herein, the first experimental study of the high‐speed ultrasound wave detection by the combinational structure of flexible MoS2 field‐effect transistor (FET) and piezoelectric device based on polyvinylidene fluoride trifluoro ethylene P(VDF‐TrFE) is reported. The proposed flexible MoS2 based FET device exhibits maximum mobility of 18.12 cm 2 Vs −1, high on/off current ratio of ≈10 5, high robustness over mechanical tests, and excellent gate‐pulsed switching behavior at different frequencies (10, 100, and 500 kHz), thus, utilized as supporting electronics to detect ultrasound wave at high‐speed. The ultrasound waves are applied to the self‐assembled piezoelectric device under different power scales (0 ≈ 1.5 W cm −2 ) and the transfer curve of the proposed FET is analyzed. The results show a clear detection of ultrasound waves with high stability and excellent linearity in terms of threshold voltage ( V th ) shift and drain current ( I ds ) under different power levels. Also, the pulsed gate‐switching behavior is analyzed and the ultrasound detection with high stability is observed at high‐speed switching, thus, enabling the development of applications in high‐speed electronic devices and biomedical imaging tools. Abstract : The first experimental study of the high‐speed ultrasound wave detection by the combinational structure of flexible MoS2 transistor and piezoelectric device is reported here. The measurement results show that this system is capable of detecting ultrasound waves at high‐speed with stable and good electrical performance, which thus demonstrates a promising potential for futuristic applications in the electronics and biomedical field.